Ketentuan Hukum Pidana dalam Upaya Menanggulangi Tindak Pidana Illegal Logging di Indonesia - Ricky Sitanggang; I Dewa Gede Dana Sugama (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The development of modern society in the process of globalization and industrialization has had a huge impact on forest sustainability as a support for life and in the world's biological life. The existence of forests is of course very much needed considering that forests are not only a source of wood production but are also an integral part of the environment, forests are open areas that make people's access to use them very large which causes logging and timber theft. In order for this to happen more often, this problem must be addressed immediately for the sake of the preservation of forest ecosystems in Indonesia. This journal writing uses normative research methods, normative methods are used with a statutory approach and use reference materials from book sources or other scientific research. As for the results of this study, the regulation of illegal logging is contained in the Law of the Republic of Indonesia Number 41 of 1999 concerning Forestry in Article 50 which regulates prohibitions for anyone who carries out activities in the form of logging, Article 50 also discusses the prohibition of carrying out forest destruction activities. and confiscation of forest resources in violation of laws and regulations or without permission from interested parties, namely forestry officials.